2017
DOI: 10.1063/1.4976681
|View full text |Cite
|
Sign up to set email alerts
|

Observing visible-range photoluminescence in GaAs nanowires modified by laser irradiation

Abstract: We study structural and chemical transformations induced by focused laser beam in GaAs nanowires with axial zincblende/wurtzite (ZB/WZ) heterostucture. The experiments are performed using a combination of transmission electron microscopy, energy-dispersive X-ray spectroscopy, Raman scattering, and photoluminescence spectroscopy. For the both components of heterostructure, laser irradiation under atmospheric air is found to produce a double surface layer which is composed of crystalline arsenic and of amorphous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…These results clearly provide evidence that the surface excess arsenic in the crystalline or amorphous forms is the origin of the surface states responsible for surface nonradiative recombination and for the surface Fermi level pinning. These observations agree with the already known results observed on the photooxidation of GaAs nanowires [24,26].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results clearly provide evidence that the surface excess arsenic in the crystalline or amorphous forms is the origin of the surface states responsible for surface nonradiative recombination and for the surface Fermi level pinning. These observations agree with the already known results observed on the photooxidation of GaAs nanowires [24,26].…”
Section: Resultssupporting
confidence: 93%
“…After irradiation of the nanowire by a beam with the power density of 500 kW/cm 2 , the band-edge PL was not detected, which indicated that the PL intensity decreased by at least 3 orders of magnitude. At the same time, a weak PL appeared near 1.8 eV, which was apparently related to the formation of the GaO x layer [26]. The observed elimination of the band-edge PL intensity arose from the entire oxidation of the core / shell interface.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to these cases, structural transitions of amorphization or transition to another crystalline state usually occur in irradiated nanostructured materials. Amorphization and cubic-hexagonal transition phenomena [16,17] of Si NWs under irradiation conditions were found by Dai et al and Rodichkina et al, while Alekseev et al [18] also showed that radiation leads to amorphization in ZB/WZ heterostructure GaAs NWs, where the WZ structure transforms into β-Ga 2 O 3 crystals. Meanwhile, there is continuous progress in the study of the mechanical properties of irradiated GaAs NWs.…”
Section: Introductionmentioning
confidence: 84%
“…In all cases mentioned above, the surface Fermi remains at the same distance of 4.8 eV from the vacuum level . Such pinning behavior was assumed to be induced by a layer of As , atoms forming at the NW surfaces because of incomplete oxidation of the III–As materials in ambient atmosphere.…”
mentioning
confidence: 99%